2021
DOI: 10.1021/acsomega.1c04107
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Fenton Process over an Fe-Free 3%-CuO/Sr0.76Ce0.16WO4 Photocatalyst under Simulated Sunlight

Abstract: Photo-Fenton is a promising photocatalytic technology that utilizes sunlight. Herein, an Fe-free 3%-CuO/Sr0.76Ce0.16WO4 photocatalyst was synthesized to apply simulated wastewater degradation via a photo-Fenton process under simulated sunlight. The photodegradation efficiency of RhB solution over the 3%-CuO/Sr0.76Ce0.16WO4 photocatalyst is 93.2% in the first 3 h; its photocatalytic efficiency remains at 91.6% even after three cycle experiments. The kinetic constant of the 3%-CuO/Sr0.76Ce0.16WO4 photocatalyst i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…This result is consistent with the high level of FLO degradation obtained with these nanoparticles, demonstrating that the incorporation of Pd into the nanoparticle structure, in addition to the promotion of electronic transfer between metals, also helps generate other radicals that make the reaction mechanism more efficient. , Finally, the effect of EDTA (holes) was assessed. It was determined that the presence of EDTA as a quenching agent affects the degradation capacity of Fe 2 O 3 -Ni-Pd, and it was also observed that, only in this case, photogenerated holes can oxidize water to form hydroxyl radicals or directly oxidize FLO, making the Fenton reaction more favorable. This result is consistent with the experiment without a quenching agent or kinetic results in which Fe 2 O 3 -Ni-Pd shows a 100% of degradation at 5 min.…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with the high level of FLO degradation obtained with these nanoparticles, demonstrating that the incorporation of Pd into the nanoparticle structure, in addition to the promotion of electronic transfer between metals, also helps generate other radicals that make the reaction mechanism more efficient. , Finally, the effect of EDTA (holes) was assessed. It was determined that the presence of EDTA as a quenching agent affects the degradation capacity of Fe 2 O 3 -Ni-Pd, and it was also observed that, only in this case, photogenerated holes can oxidize water to form hydroxyl radicals or directly oxidize FLO, making the Fenton reaction more favorable. This result is consistent with the experiment without a quenching agent or kinetic results in which Fe 2 O 3 -Ni-Pd shows a 100% of degradation at 5 min.…”
Section: Resultsmentioning
confidence: 99%